Analisis Perencanaan Pajak Penghasilan Pasal 21 Untuk Mengoptimalkan Penghematan Pajak Penghasilan Badan Pada Pt Infra Digital Nusantara Jakarta Tahun 2021 - Fathiyah Choirunnisa; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2023)
The phenomenon that occurs at PT Infra Digital Nusantara, is in the calculation  of Article 21 income  tax,  the  company  takes  practical steps using the gross method so that there are  no corporate  income tax savings. This study has a concern  on three  issues they are,  the application  of tax planning as an effort to optimize employee income tax at PT Infra Digital Nusantara in 2021, the tax planning  carried out  is  in  accordance  with  applicable   tax  regulations,   and   the corporate  tax savings obtained as implications of the gross-up method strategy   applied.   The   research    method   used   is   a   qualitative descriptive  approach  using data  collection  techniques  by means of observation, interviews, documentation and triangulation. The results of the study indicate that PT Infra Digital Nusantara has carried  out Article 21 income tax planning well. Does not violate tar provisions, in  the  business  is  already   rational   and  has  been  supported   by adequate  supporting  evidence.  Tax planning  in  the  calculation   of income tax Article 21 carried  out by PT Infra Digital Nusantara with the  gross  method  has  been  in  accordance  with  the  provisions  of taxation  formally and materially.  There is no corporate  income tax savings on income tax Article 21 planning  with the gross up method carried  out at PT Infra  Digital  Nusantara, but tax savings can  be obtained for the following tax year. For a loss of Rp11,866,031,959 in  2021,  which  is greater  than  4.02%,  it can  compensate  for  the company's profits in the following years, so that the payment of corporate  tax can be lower